From somatostatin to octreotide LAR: evolution of a somatostatin analogue - Anthony, Lowell (2009)
BACKGROUND: Acromegaly is characterized by overproduction of growth hormone (GH) by the pituitary gland. GH stimulates the synthesis of insulin-like growth factor-I (IGF-I), and the somatic growth and metabolic dysfunction that characterize acromegaly are a consequence of elevated GH and IGF-I levels. Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are rare, slow-growing neoplasms that have usually metastasized by the time of diagnosis. The majority of GEP-NETs are carcinoid tumors whose syndrome is caused by the hypersecretion of biogenic amines, peptides and polypeptides responsible for the principal symptoms of diarrhea and flushing. METHODS: The MEDLINE and EMBASE databases were searched for preclinical and clinical studies of octreotide (Sandostatin), a potent synthetic somatostatin analogue, in patients with acromegaly or GEP-NETs. OBJECTIVE: This article reviews the 20 years of clinical experience with octreotide and the impact it has made in patients with acromegaly or GEP-NETs. RESULTS: Octreotide has proven to be an essential component in the management strategy of acromegaly and GEP-NETs over the past 20 years. The multiple beneficial effects of octreotide throughout the body, combined with its established safety profile (the most common adverse effects are injection-site pain and gastrointestinal events), have made it an appealing option for clinicians. The advent of the long-acting release (LAR) formulation of octreotide provided additional benefits to patients through monthly administration, while maintaining the efficacy and tolerability profile of the daily subcutaneous formulation. CONCLUSIONS: Octreotide is a potent synthetic somatostatin analogue that has become the mainstay of medical therapy for tumor control in neuroendocrine disorders such as acromegaly and GEP-NETs. The development of octreotide LAR offered a further advancement; less frequent dosing provided valuable benefits in quality of life to patients, with equivalent efficacy and tolerability. Moreover, recent results from the PROMID study have confirmed the antiproliferative effect of octreotide LAR in patients with well-differentiated metastatic GEP-NETs of the midgut. New therapeutic uses of octreotide are currently under investigation in a variety of clinical settings.